Teorisasi Tafsir Maqasidi dan Arah Pengembangannya Menurut Mufasir Kontemporer: Komparasi Wasfi ‘Asyur dan Abdul Mustaqim: The Theory of Maqasidi Interpretation and Its Developmental Trajectory According to Contemporary Mufassir: A Comparative Analysis of Wasfi ‘Asyur and Abdul Mustaqim - Ahmad Zaeni (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2026)
Tafsir Maqasidi, as an interpretation considered relatively new, necessitates theorization, both ontologically and epistemologically. Wasfi Asyur and Abdul Mustaqim are contemporary thinkers who have theorized Tafsir Maqasidi. The purpose of this research is to construct the theorization of Tafsir Maqasidi in the contemporary era in its ontological and epistemological aspects, with the thoughts of Wasfi Asyur and Abdul Mustaqim as the model while exploring the opportunities for the direction of development of the theory of Tafsir Maqasidi according to both of them. The method used is descriptive, while the analysis used is subjective hermeneutics. Descriptive methods are used to describe the research data, and the results are accompanied by pictures or tables, while subjective hermeneutics is used to understand the thoughts of the two figures from the researcher's perspective and experience. There are two research questions answered: first, how is the comparison of the theorization of Tafsir Maqasidi between Wasfi Asyur and Abdul Mustaqim; and second, what are the opportunities for the direction of development of the theory of Tafsir Maqasidi according to both of them? Researcher found that ontologically and epistemologically, the theorization of Tafsir Maqasidi version of Wasfi Asyur refers to the rules of Usuliyyah and Maqasid al-Syariah, while the theorization of Tafsir Maqasidi version of Abdul Mustaqim refers to Maqasid al-Syariah and hermeneutics.